CRISIS RESOLUTION IN THE FIELD OF THE FINANCIAL PRUDENTIAL SUPERVISION – SOME LEGAL AND ECONOMIC ASPECTS - Sipos, Ágnes; Kovács, Tamás (European Scientific Journal, ESJ, 2014)
The financial crisis of 2008 has challenged fundamental ideological changes among the financial policy makers and the regulatory authorities. The financial crisis was only “indicator” in the configuration of the new financial supervision framework of the EU, because it was the real need of the international financial markets, formed as a result of the change in the past decades. The aim of the paper is to outline the causes and most important features of the global financial crisis and to introduce the evolving crisis management programs from the aspect of monetary and financial law regulation. Besides we introduce the newly established authorities of financial supervision at EU level and the legal method, the regulation of the Directive 2014/59/EU of 15 May 2014 establishing a framework for the recovery and resolution of credit institutions and investment firms. The main conclusion of our paper is that the financial crisis may mark a new era and result a paradigmatic change in the relationship of the markets, not only in the field of financial economy, but at the field of law sciences as well.